Human dental enamel evaluation after radiotherapy simulation and laminates debonding with Er,Cr:YSGG using SEM and EDS - Rabelo, Thais Freitas; Zamataro, Claudia Bianchi; Kuchar, Nielsen Grosko; Zanini, Nathalia; Juvino, Amanda Caramel; del-Valle, Matheus; Castro, Pedro Arthur Augusto; Santos, Moises Oliveira; Zezell, Denise Maria (Journal of Oral Diagnosis, 2019)
The pursuit of perfection makes younger people undergo aesthetic procedures without formal indication. However, young patients may be susceptible to a disease such as head and neck cancer which treatment can compromise the adhesion of these indirect mate- rials. Here, we present an analyze, of the gamma radiation effects on crystallographic morphology of human dental enamel after laminate veneer debonding with Er,Cr:YSGG laser. Thus, human dental enamel samples were prepared and randomized into 2 groups (n=10): Laser Irradiation (L) and Gamma + Laser Irradiation (GL) group. Scanning elec- tron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were performed before bonding and after debonding using Er,Cr:YSGG. Only Gamma + Laser Irradia- tion group received a cumulative dose of 70 Gy gamma radiation used in head and neck cancer radiotherapy. SEM images showed that both GL and L groups presented altered morphology. EDS showed an decrease in Ca and P intensities after laser debonding of laminates veneers in both group. Therefore, a proper laser facet removal protocol should be established for healthy patients and patients who have been exposed to radiotherapy for head and neck cancer.